Regenerative nanomedicine: current perspectives and future directions - Chaudhury K (Dove Medical Press, 2014)
Koel Chaudhury, Vishu Kumar, Jayaprakash Kandasamy, Sourav RoyChoudhurySchool of Medical Science and Technology, Indian Institute of Technology, Kharagpur, West Bengal, IndiaAbstract: Nanotechnology has considerably accelerated the growth of regenerative medicine in recent years. Application of nanotechnology in regenerative medicine has revolutionized the designing of grafts and scaffolds which has resulted in new grafts/scaffold systems having significantly enhanced cellular and tissue regenerative properties. Since the cell–cell and cell-matrix interaction in biological systems takes place at the nanoscale level, the application of nanotechnology gives an edge in modifying the cellular function and/or matrix function in a more desired way to mimic the native tissue/organ. In this review, we focus on the nanotechnology-based recent advances and trends in regenerative medicine and discussed under individual organ systems including bone, cartilage, nerve, skin, teeth, myocardium, liver and eye. Recent studies that are related to the design of various types of nanostructured scaffolds and incorporation of nanomaterials into the matrices are reported. We have also documented reports where these materials and matrices have been compared for their better biocompatibility and efficacy in supporting the damaged tissue. In addition to the recent developments, future directions and possible challenges in translating the findings from bench to bedside are outlined.Keywords: regenerative medicine, nanomedicine, nanotechnology